Rheb-mTOR activation rescues Aβ-induced cognitive impairment and memory function by restoring miR-146 activity in glial cells - Dipayan De; Ishita Mukherjee; Subhalakshmi Guha; Ramesh Kumar Paidi; Saikat Chakrabarti; Subhas C. Biswas; Suvendra N. Bhattacharyya (Elsevier, 2021)
Deposition of amyloid beta plaques in adult rat or human brain is associated with increased production of proinflammatory cytokines by associated glial cells that are responsible for degeneration of the diseased tissue. The expression of these cytokines is usually under check and is controlled at the post-transcriptional level via several microRNAs. Computational analysis of gene expression profiles of cortical regions of Alzheimer's disease patients' brain suggests ineffective target cytokine mRNA suppression by existing micro-ribonucleoproteins (miRNPs) in diseased brain. Exploring the mechanism of amyloid beta-induced cytokine expression, we have identified how the inactivation of the repressive miR-146 miRNPs causes increased production of cytokines in amyloid beta-exposed glial cells. In exploration of the cause of miRNP inactivation, we have noted amyloid beta oligomer-induced sequestration of the mTORC1 complex to early endosomes that results in decreased Ago2 phosphorylation, limited Ago2-miRNA uncoupling, and retarded Ago2-cytokine mRNA interaction in rat astrocytes. Interestingly, constitutive activation of mTORC1 by Rheb activator restricts proinflammatory cytokine production by reactivating miR-146 miRNPs in amyloid beta-exposed glial cells to rescue the disease phenotype in the in vivo rat model of Alzheimer's disease.